IMPLEMENTASI KEBIJAKAN LINGKUNGAN DALAM PENGEMBANGAN EKOWISATA EMBUNG TERPADU DAYUN KECAMATAN DAYUN KABUPATEN SIAK : PERSEPEKTIF KOLABORASI PENTAHELIX - Sri Wahyu Ningsih; Aprilia Atika Putri; Zulkarnaini (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2025)
This study aims to analyze the implementation of environmental policies in the development of the Dayun Integrated Reservoir Ecotourism in Siak Regency through a pentahelix collaboration approach. This study used a descriptive qualitative approach, with data collection techniques including observation and interviews with actors involved in ecotourism management. The results indicate that environmental policies have a strong legal basis, but their implementation at the local level remains partial and not systematically integrated. Collaboration between pentahelix actors (government, academics, business actors, communities, and the media) has been established, but remains weak in terms of coordination, institutional capacity, and funding infrastructure. This study recommends the establishment of a permanent collaboration forum, the development of village regulations specifically for environmental management, and community capacity building through environmental education and training.